Education in post-classical era - Nina V. Nalivayko (Высшее образование в России, 2022)
The review takes up the key issues elaborated in the monograph “Educational Institution, Power and Society in the Age of Knowledge Culture Growth” (A.O. Karpov). These key issues include: the leading role of research education in the process of the new technological setup formation; processes of knowledge culture deconstruction and the policy of education commodification, in particular; the fundamentals of cognitive and cultural polymorphism of educational systems, well-grounded by the analysis of ethno-diversification models and socio-cognitive specific features typical for the society of knowledge; paradigmatically differentiated structure of modern education. Special mention of the high significance of the material presented in the text of the monograph has been made.